DDDR-32. A NEW IMMUNOMODULATORY FUNCTION OF PYRIDO-PYRIMIDINE DERIVATIVES TO IMPAIR METASTATIC GROUP 3 MEDULLOBLASTOMA IN VIVO. (14th November 2022) - Zollo, Massimo; Asadzadeh, Fatemeh; Ferrucci, Veronica; De Antonellis, Pasqualino; Bibbò, Francesca; Siciliano, Roberto; Sorice, Carmen; Criscuolo, Giuseppina; Filiz, Dalim Kardelen; Tecik, Melisa; Amente, Stefano; Saccà, Carmen Daniela; et al.
Abstract: Medulloblastoma (MB) is an embryonal tumor of the cerebellum constituting 20% of pediatric brain tumors. To date, four MB molecular groups (further stratified in twelve subtypes) have been described. Among them, Groups 3 and Group 4 MB have the poorest prognosis due to their high metastatic potential. Recently, we have reported a metastatic axis driven by Prune1 overexpression in MB Group3 characterized by canonical TGF-β signaling enhancement and epithelial-mesenchymal transition. Here, we have developed a new not toxic pyrido-pyrimidine derivative with the ability to impair Prune-1-driven-axis, thus ameliorating the survival rate of a murine model of metastatic MB Group3 characterized by overexpression of human Prune1 gene in the cerebellum (under the control of MATH1 promoter). Of importance, this small molecule also is showing immunomodulatory functions thus inhibiting the conversion of tumor-infiltrating T lymphocytes (TILs) to immunosuppressive regulatory T cells (Tregs ) in vivo via impairing the secretion of inflammatory cytokines from MB cells. Furthermore, this molecule can also act synergistically with the currently used modified-intensity chemotherapy (e.g. in PNET5 use of Vincristine) or potential in the combination with epigenetics drugs (e.g., LSD1/KDM1A inhibitors). Altogether these results are of importance for future targeted therapies of high-risk metastatic MB. Acknowledgments: We thank for funding support: the Italian Association for Cancer Research (AIRC) Grant IG no. 22129 (M.Z.) and Lazio Innova Grant n. 85-2017-14785 (FT; MZ)